From the Chattel to the Cattle: Human and Animal Laborers in Ancient Israel and Its Context - Millar, Suzanna (Journal of Biblical literature, 2024)
In many cultures through history, subjugated human and animal laborers have been treated alike. However, very little research has explored this connection in relation to ancient Israel and Judah or ancient West Asia more broadly. In this article, I analyze the interconnections between institutions of human and animal labor according to biblical and other West Asian evidence. Physically, slaves and livestock were subjected to the same body modifications (such as brandings and piercings) and the same physical beatings. Economically, both groups were central to transactions, being bought, sold, or forcibly taken, and laboring for their masters. Socially, both groups were drawn in to participate in societies and nations, and they were precariously situated in kinship groups. Psychologically, both may have been kept in place by their masters' Social Dominance Orientation, and slaves may have been animalized to justify their treatment. In these ways, institutions of human and animal labor were entangled and mutually reinforcing, leading to the subjugation of both the chattel and the cattle.